Exploring the impact of AI-enhanced virtual tourism on Tourists' pro-environmental behavior: A stimulus-organism-response model perspective - Suihui Wu; Siyao Wang (Acta Psychologica)
This study explores the potential of AI-enhanced virtual tourism to promote pro-environmental behavior (PEB) in cultural heritage tourism in China. Employing the stimulus-organism-response (SOR) model, we examine how five stimuli—accessibility, authenticity perceptions, perceived costs, interactive experiences, and knowledge acquisition—affect tourists' attitudes toward AI-enhanced virtual tourism and, consequently, their environmental behaviors. We conducted a partial least squares structural equation modeling (PLS-SEM) using Smart-PLS to analyze the two-wave survey data collected from 223 tourists. Our results confirmed that accessibility, authenticity perceptions, interactivity, and knowledge acquisition significantly influence tourists' attitude, which further influences PEB. The findings contribute to the theoretical understanding of technology-mediated sustainable tourism by highlighting the mediating role of attitude in the relationship between AI-enhanced virtual tourism experiences and PEB. The study provides practical insights for the development of such tourism experiences that not only enhance tourist engagement but also support environmental sustainability.